Journalism and rugby in Spain: from scholarly omission to digital self-affirmation and thematic feminization - Sapag M., Pablo; Recio García, Armando (Historia y Comunicación Social, 2026)
Rugby is already a globalized and media-dependent sport with scholarly attention. What is not yet established are the aspects that scientific research focuses on, particularly the relation between specialized journalism and rugby. This work set up the sources for a history of Spanish rugby journalism and determines the state of the sport in Spain within a global framework of professionalization, feminization, and TV broadcasting and digital media dependence. After analyzing rugby-related publications, it is concluded that they have a fourfold focus: rugby versus football; Spanish versus global one; specialized journalism in a country where beside football other sports got specialized coverage; and as independent publications versus institutional ones, especially those of the Spanish Rugby Federation.